Aspalathin-rich green rooibos tea in combination with glyburide and atorvastatin enhances lipid metabolism in a db/db mouse model - Patel, Oelfah; Muller, Christo J. F.; Joubert, Elizabeth; Rosenkranz, Bernd; Louw, Johan; Awortwe, Charles (Frontiers in Clinical Diabetes and Healthcare, 2022)
Rooibos (Aspalathus linearis), an indigenous South African plant and its major flavonoid, aspalathin, exhibited positive effects on glycemia and dyslipidemia in animal studies. Limited evidence exists on the effects of rooibos extract taken in combination with oral hypoglycemic and lipid-lowering medications. This study investigated the combined effects of a pharmaceutical grade aspalathin-rich green rooibos extract (GRT) with the sulfonylurea, glyburide, and atorvastatin in a type 2 diabetic (db/db) mouse model. Six-week-old male db/db mice and their nondiabetic lean db+ littermates were divided into 8 experimental groups (n=6/group). Db/db mice were treated orally with glyburide (5 mg/kg bodyweight), atorvastatin (80 mg/kg bodyweight) and GRT (100 mg/kg bodyweight) as mono- and combination therapies respectively, for 5 weeks. An intraperitoneal glucose tolerance test was conducted at 3 weeks of treatment. Serum was collected for lipid analyses and liver tissues for histological examination and gene expression. A significant increase in the fasting plasma glucose (FPG) of the db/db mice compared to their lean counterparts (from 7.98 ± 0.83 to 26.44 ± 1.84, p < 0.0001) was observed. Atorvastatin reduced cholesterol (from 4.00 ± 0.12 to 2.93 ± 0.13, p < 0.05) and triglyceride levels (from 2.77 ± 0.50 to 1.48 ± 0.23, p < 0.05). In db/db mice, the hypotriglyceridemic effect of atorvastatin was enhanced when combined with both GRT and glyburide (from 2.77 ± 0.50 to 1.73 ± 0.35, p = 0.0002). Glyburide reduced the severity and pattern of steatotic lipid droplet accumulation from a mediovesicular type across all lobular areas, whilst combining GRT with glyburide reduced the abundance and severity of lipid droplet accumulation in the centri- and mediolobular areas. The combination of GRT, glyburide and atorvastatin reduced the abundance and severity of lipid accumulation and the intensity score compared to the administered drugs alone. The addition of either GRT or glyburide in combination with atorvastatin had no effect on blood glucose or lipid profiles, but significantly reduced lipid droplet accumulation.